Temperature‐Dependent and pH‐Responsive Pillar[5]arene‐Based Complexes and Hydrogen‐Bond‐Based Supramolecular Pentagonal Boxes in Water. Issue 49 (10th August 2020) - Hadar, Maya; Kaizerman‐Kane, Dana; Zafrani, Yossi; Cohen, Yoram
Abstract: Supramolecular systems in water are of paramount importance and those based on hydrogen bonds are both intriguing and scarce. Here, after studying the peculiar host–guest complexes formed between per‐dimethylamino‐pillar[5]arene (1 ) and the bis‐sulfonates 2 a –c, we describe the formation of the first hydrogen‐bond‐based supramolecular pentagonal boxes (SPBs), which are stable in water. These pH‐responsive SPBs are constructed from 1 as a body, benzene polycarboxylic acids 3 a, b as lid compounds, and 2 a –c as guests. We demonstrate that encapsulation of 2 a –c in pillar[5]arene 1 and in the highly stable water‐soluble SPBs, that is, 1(3 a) 2 and 1(3 b) 2, is both temperature and pH dependent and, quite interestingly, depends, on the nature of the lid compounds used for capping the boxes even at high pH. We also highlight the difference in the 1 H NMR characteristics of 2 b and 2 c in the cavity of 1 and the SPBs. Abstract : Trapped in a box : Temperature‐dependent and pH‐responsive water‐soluble complexes and supramolecular pentagonal boxes (SPBs) based on per‐amino‐pillar[5]arene were prepared for the first time. These complexes and hydrogen‐bond‐based SPBs are highly stable in water and the guest encapsulation in these systems was found to be both temperature and pH depended, and is also affected by the nature of the lid compound used for capping the boxes.